MOTIVASI WARGA BELAJAR MENGIKUTI PELAKSANAAN PEMBELAJARAN KETERAMPILAN OTOMOTIF DAN TEKNIK PENGELASAN DI PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI, PEKANBARU - Gita Roza Novilda; Aswandi Bahar; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research it is based on encouragement mental generate and directing the behavior of learnin. Formulation problems in this research was how high motivation residents learn follow learning skill automotive and techniques welding in Panti Sosial Bina Remaja (PSBR) Rumbai, Pekanbaru. So the purpose of this research is to know the level motivation residents learn follow learning skill automotive and techniques welding in Panti Sosial Bina Remaja (PSBR) Rumbai, Pekanbaru. And the usefulness of this research, can provide the understanding of presentation weighting skill automotive and techniques welding to the people learn about presentation weighting skill automotive and techniques welding. The sample techniques used technique sampling saturated. The taking of engineering data in this study is a technique poll, that is the sum of 60 statemen. Data is collected from the respondents who consist of 20 people residents learn for a sample of the test and 34 people learn to the study sample. motivation residents learn follow learning skill automotive and techniques welding in Panti Sosial Bina Remaja (PSBR) Rumbai, Pekanbaru High with the rata-rata whole (SB+B) 75 %. So it can also be drawn the conclusion that, motivation residents learn follow learning automotive skills and techniques of welding in Sosial Bina Remaja (PSBR) Rumbai, Pekanbaru High. It means residents learn motivated to study because want to be a can be dependent and can take advantage of leisure a good.Key words: motivation, Motivation residents learning